Submillimeter mapping of mesospheric minor species on Venus with ALMA. (August 2015) - Encrenaz, T.; Moreno, R.; Moullet, A.; Lellouch, E.; Fouchet, T.
Abstract: Millimeter and submillimeter heterodyne spectroscopy offers the possibility of probing the mesosphere of Venus and monitoring minor species and winds. ALMA presents a unique opportunity to map mesospheric species of Venus. During Cycle 0, we have observed Venus on November 14 and 15, 2011, using the compact configuration of ALMA. The diameter of Venus was 11″ and the illumination factor was about 90%. Maps of CO, SO, SO2 and HDO have been built from transitions recorded in the 335–347 GHz frequency range. A mean mesospheric thermal profile has been inferred from the analysis of the CO transition at the disk center, to be used in support of minor species retrieval. Maps of SO and SO2 abundance show significant local variations over the disk and contrast variations by as much as a factor 4. In the case of SO2, the spatial distribution appears more "patchy", i.e. shows short-scale structures apparently disconnected from day-side and latitudinal variations. For both molecules, significant changes occur over a timescale of one day. From the disk averaged spectrum of SO recorded on November 14 at 346.528 GHz, we find that the best fit is obtained with a cutoff in the SO vertical distribution at 88±2 km and a uniform mixing ratio of 8.0±2.0 ppb above this level. The SO2 map of November 14, derived from the weaker transition at 346.652 GHz, shows a clear maximum in the morning side at low latitudes, which is less visible in the map of November 15. We find that the best fit for SO2 is obtained for a cutoff in the vertical distribution at 88±3 km and a uniform mixing ratio of 12.0±3.5 ppb above this level. The HDO maps retrieved from the 335.395 GHz show some enhancement in the northern hemisphere, but less contrasted variations than for the sulfur species maps, with little change between November 14 and 15. Assuming a typical D/H ratio of 200 times the terrestrial value in the mesosphere of Venus, we find that the disk averaged HDO spectrum is best fitted with a uniform H2 O mixing ratio of 2.5±0.6 ppm (corresponding to a HDO mixing ratio of 0.165±0.040 ppm). We note that our spectrum is also compatible with a H2 O mixing ratio of 1.5 ppm in the 80–90 km altitude range, and a mixing ratio of 3 ppm outside this range, as suggested by the photochemical model of Zhang et al. (2012, Icarus, vol. 217, pp. 714–739). Our results are in good general agreement with previous single dish submillimeter observations of Sandor and Clancy (2005, Icarus, vol. 177, pp. 129–143), Gurwell et al. (2007, Icarus, vol. 188, p. 288), and Sandor et al. (2010, Icarus, vol. 208, pp. 49–60; 2012, Icarus, vol. 217, pp. 839–844 ) and with SPICAV/Venus Express results of Fedorova et al. (2008, J. Geophys. Res., vol. 113, p. E00B25) and Belyaev et al. (2012). Highlights: This paper presents the first maps of minor species in the mesosphere of Venus. Data were recorded with the Atacama Large Millimeter Array in November 2011. The SO and SO2 maps show strong spatial and short-term temporal variations. These results are compared with Venus Express and ground-based observations.